ANALISIS PENGARUH CURRENT RATIO (CR) DAN NON PERFORMING LOAN (NPL) TERHADAP RETURN ON ASET (ROA) PADA PT. BANK BNI TBK PERIODE 2013-2020 - Silaban, Frederick; Silaban, Pasaman (Media Mahardhika, 2025)
The purpose of this study is to determine the simultaneous influence of the current ratio (CR) and non-performing loans (NPL) on return on assets (ROA) at PT Bank BNI. The research method is quantitative. The population used in this study is the financial statement data of Bank BNI Tbk since it went public. Purpose sampling was used, along with sample data from quarterly financial statements from the first quarter of 2013 to the fourth quarter of 2020. , the researchers used 32 samples. The results showed that the independent variables, Current Ratio (CR) and Non-Performing Loan (NPL), had a significant effect on Return on Assets (ROA). The Current Ratio (CR) had a significant effect on ROA, with a result of 1.254 and a significance value of 0.000 (<0.05). The results show that the independent variable has a significant effect on ROA with a result of 4,840 and a significance value of 0.000 <0.05. The results also show that the independent variable NPL has a significant effect on ROA with a result of 2,127 and a significance value of 0.000 <0.05. The results of the coefficient of determination test show that 32.9% of the variation is explained by the model, while the remaining 67.1% is influenced by other factors. The results of the F-test also show that the Current Ratio (CR) and Non-Performing Loan (NPL) variables have a significant effect of 4,567 and a sig. value of 0.000 < 0.05.